Transformation of Learning Kinematics of Rectilinear Motion: Essential Microcontroller-Based Experimental Tools to Improve High School Students' Understanding of Concepts - Fauza, Naila; Nurvana, Resti; Nasir, Muhammad (Kasuari: Physics Education Journal (KPEJ), 2025)
The transformation of kinematics learning requires innovative approaches to enhance students' in-depth conceptual understanding. This study aims to analyze the need to develop a microcontroller-based experimental tool for linear motion kinematics to overcome students' difficulties in understanding kinematics concepts. The study employs a qualitative descriptive approach, with data collected through interviews, questionnaires, and observations involving teachers and students from several high schools in Pekanbaru City. Data were obtained from 5 physics teachers and 30 high school students in grade XII who had previously studied linear motion kinematics. The findings indicate that students' understanding of linear motion kinematics concepts remains low, highlighting the need for a microcontroller-based experimental tool to support more interactive, accurate, and data-driven learning. This tool is expected to provide real-time visualization of kinematics parameters such as velocity, acceleration, time, and distance, facilitating students' comprehension of the relationships among these variables. This study recommends the development of a microcontroller-based experimental tool for linear motion kinematics as a strategic step to support the transformation of physics learning aligned with the demands of education in the digital era.